(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Debating the understanding and use of historical content as fact and/or fiction in publications has come a long way in the science of History (historiography). Arthur Marwick for example, in “The new nature of history, knowledge, evidence, language” provides, amongst others, insight into aspects of fact and fiction in writing (and certainly so in teaching) as part of the “eight battles” historians usually face.2 To what lengths historians and educators of History in South Africa have contributed to voices and views in research on features of fact and fiction (concepts also associated with “truth” or truthfulness “cum veracity”) regarding the country’s past will be the key focus of the paper. Eight South African journals have been scrutinised for thoughts and notions of academia (as authors of articles) regarding their way of going about with particular histories and their associations with veracity, or their criticism against past histories because of an absence or lack of veracity. The general stand of the author is that educators of History must also be sensitised to the realities of onesided factual exchange or a sense of fiction-creating in past knowledge, used as sources in Further and Higher Education and Training environments. The quest is that educators must also sensitise their students of History and Education History to be sufficiently informed and efficiently prepared when reading and using sources related to History in the classroom. Critical reading seems to be a way to become prepared to address the level of veracity of published historical research. Hands-on guidance towards critical reading will be briefly shared in the last part of the discussion.